PERANCANGAN INCUBATOR TELUR PUYUH OTOMATIS BERBASIS IOT - Ardiniansyah, Alvin; Nofitasari, Nofitasari; Riyanto, Bagus; Hariansyah, Muhammad (Journal of Informatics and Computer Engineering Research, 2025)
The success rate of quail egg hatching is highly dependent on the stability of temperature, humidity, and frequency of egg turning during the incubation period. Conventional incubators that are still widely used by small farmers tend to be less efficient because they rely on manual supervision, which can cause fluctuations in the incubation environment. Therefore, this study aims to design and compare the performance of an automatic quail egg incubator based on the Internet of Things (IoT) with a conventional manual system. The prototype of the automatic incubator uses an ESP32 microcontroller, DHT22 sensor, servo motor for egg rotation, and the Blynk application for remote monitoring. Testing was carried out for 18 days by comparing temperature, humidity, hatching power, and hatching weight between the two systems. The results showed that the IoT incubator was able to maintain a stable temperature in the range of 37.5–38°C with a fluctuation of ±0.3°C and produced a hatching power of 88%, higher than the conventional incubator which only reached 68%. The average hatching weight in the automatic incubator was also greater, namely 7.4 grams compared to 7.0 grams in the manual system. Based on these results, the application of IoT technology has been proven to increase the efficiency of the hatching process and reduce the need for manual monitoring. This innovation can be an appropriate solution in modernizing small to medium-scale poultry farms.